The Effect of Using Scrabble Media on Students’ Achievement in Vocabulary - Selamat Husni Hasibuan (Hasanuddin University, 2018)
The objectives of the research were to find out the significant effect of Using Scrabble Media which was focused on vocabulary Achievement. The research design in this research was quantitative experimental research. This research was conducted at SMP Negeri 24 Medan in academic years 2017/2018. The population of this research was in the seventh grade students which consisted of eight classes namely: Class VII-A, VII-B, VII-C, VII-D, VII-E, VII-F, VII-G and VII-H. The total numbers of population were 288 students. The research classes were divided into two classes, Experimental Class (36 students) and Control Class (36 students).The technique used was purposive sampling to determine the experimental and control group. The sample were divided into two groups, the first group VII-H which consisted of 36 students was Experimental group which was given treatment by Using Scrabble Media and second group VII-F which consisted of 36 students was Control group which was given treatment by using Conventional Method. Each group was given a pre-test, treatment and post-test. The t-test was 15,71 and the t-table was 1.68 and 0.05 was as the significant level of this research. Because the t-test value was higher than t-table (15,71 > 1.68). It showed that the result in t-test was accepted (Ha). Based on the result of this research, it could be concluded that there was significant effect of Using Scrabble Media on the Students’ Achievement in vocabulary